The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.optcom.2008.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Slow-light enhanced light–matter interactions with applications to gas sensing

Abstract: Optical gas detection in microsystems is limited by the short micron scale optical path length available. Recently, the concept of slow-light enhanced absorption has been proposed as a route to compensate for the short path length in miniaturized absorption cells. We extend the previous perturbation theory to the case of a Bragg stack infiltrated by a spectrally strongly dispersive gas with a narrow and distinct absorption peak. We show that considerable signal enhancement is possible. As an example, we consid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Recent works [7,8] have theoretically demonstrated that Beer-Lambert-Bouguer (BLB) absorption can be increased while light transmits through a special kind of microstructured photonic crystal (PC) cuvette. This absorption enhancement was attributed in [7,8] to the slow group velocity in the cuvette. A simpler interpretation of these results would be that the PC structure acts as a quasi-cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works [7,8] have theoretically demonstrated that Beer-Lambert-Bouguer (BLB) absorption can be increased while light transmits through a special kind of microstructured photonic crystal (PC) cuvette. This absorption enhancement was attributed in [7,8] to the slow group velocity in the cuvette. A simpler interpretation of these results would be that the PC structure acts as a quasi-cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the dependence of the optical absorption of molecules on the group velocity is radically different depending on the slowlight generation mechanism, this clarifies that the group velocity is not the appropriate universal quantity scaling lightmatter interactions. In a periodic, lossless media such as ring resonators the velocity of energy propagation is identical to the group velocity of a quasi-monochromatic wave [14][15][16][17][18] [8,9]. Reducing the electromagnetic energy velocity through structural slow light effectively increases the electromagnetic energy density and yields the observed enhancement of light-matter interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of slow light in gyroscopes has also been theoretically investigated 5 and the possibility to use fiber Bragg gratings to realize ultrasensitive strain sensors has been experimentally proved 6 . Recent works 7,8 have theoretically demonstrated that BeerLambert-Bouguer (BLB) absorption can be increased while light transmits through a special kind of microstructured photonic crystal (PC) cuvette. This absorption enhancement was attributed in these works 7,8 to the slow group velocity in the cuvette.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A one-dimensional Bragg stack [8] is one example of a structure that can enhance the net absorption experienced by a beam traversing the structure. In this case, the picture of a beam propagation path that is effectively prolonged by multiple back-and-forth scattering in the propagation direction offers a simple physical interpretation.…”
Section: Introductionmentioning
confidence: 99%